1995
DOI: 10.1227/00006123-199510000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Combined Molecular Genetic Studies of Chromosome 22q and the Neurofibromatosis Type 2 Gene in Central Nervous System Tumors

Abstract: Monosomy of chromosome 22 or deletions of 22q have been described in meningiomas and astrocytic tumors, the incidence of which is increased in Type 2 neurofibromatosis. Recently, the gene for neurofibromatosis Type 2 (NF2) has been identified at Chromosome 22q12, and a tumor suppression role has been suggested. Because there have been only a few studies of the NF2 gene on central nervous system tumors other than vestibular schwannomas, we investigated the potential role of NF2 as a tumor suppressor gene in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Alternatively, such dysplastic abnormalities may represent random developmental events, without an environmental trigger. This raises the possibility of somatic mutations in genes critical for cortical development, as suggested for sporadic meningiomas where somatic mutations in the NF2 gene occur 23…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, such dysplastic abnormalities may represent random developmental events, without an environmental trigger. This raises the possibility of somatic mutations in genes critical for cortical development, as suggested for sporadic meningiomas where somatic mutations in the NF2 gene occur 23…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of meningioma is a complex process associated with an accumulation of various genetic and epigenetic alterations that occur during the initiation and progression of the tumor ( 7 ). Monosomy 22, 22q deletion and/or mutation of the neurofibromatosis type 2 gene have been identified as important initiating events and represent the most common genetic alterations in meningiomas ( 8 10 ). Other common chromosomal alterations include deletions of 1p, 6q, 10q and 14q, and insertions of 1q, 9q, 12q, 15q, 17q and 20q ( 7 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For non‐ NF2 /22q tumors in this cohort, CDKN2A/B homozygous deletion, 1q gain, 3p loss, 18q loss and ALT were found to be common molecular changes developing in recurrences. Goutagny et al [ 13 ] also found a higher burden of cytogenetic alterations in NF2 ‐mutant meningiomas and Bi et al [ 6 ] showed similar findings among higher‐grades meningiomas with 22q loss. We appreciate that more than one locus may be gained or lost at a specific chromosomal arm.…”
Section: Discussionmentioning
confidence: 78%
“…Aetiologically, it has been known for a long time that neurofibromatosis type 2 ( NF2 ) gene located on chromosome 22q is lost or mutated in up to half of all meningiomas [ 2 , 11 , 12 , 13 ]. NF2 inactivation is regarded as an early event in meningiomagenesis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%